Combined performance studies for electrons at the 2004 ATLAS combined test-beam - Onofre, A. (2010)
In 2004 at the ATLAS (A Toroidal LHC ApparatuS) combined test beam, one slice of the ATLAS barrel detector (including an Inner Detector set-up and the Liquid Argon calorimeter) was exposed to particles from the H8 SPS beam line at CERN. It was the first occasion to test the combined electron performance of ATLAS. This paper presents results obtained for the momentum measurement p with the Inner Detector and for the performance of the electron measurement with the LAr calorimeter (energy E linearity and resolution) in the presence of a magnetic field in the Inner Detector for momenta ranging from 20 GeV/c to 100 GeV/c. Furthermore the particle identification capabilities of the Transition Radiation Tracker, Bremsstrahlungs-recovery algorithms relying on the LAr calorimeter and results obtained for the E/p ratio and a way how to extract scale parameters will be discussed.